The Role of Innovation in the Development of Cross-Border Cooperation: Potential and Growth Guidance in the EAEU - Yury A. Tikhomirov (RUDN Journal of Economics)
The focus of this research is the problem of insufficient elaboration of applied issues of world trade and international economic relations of neighboring countries. The study is aimed at determining the development potential of cross-border economic cooperation of the EAEU member countries and the guidelines for its growth. The methodological apparatus of the research covers methods of regression and correlation analysis, structural analysis and forecasting. The core of the empirical part of the study is a factor analysis of cross-border cooperation between countries within the EAEU, which is carried out based on statistics from the International Trade Center and WIPO for 2019-2021. A scientific search is being carried out for such a combination of innovation economy factors that would achieve the maximum share of the EAEU in the structure of Russia’s international trade. As a result, an econometric model was compiled of the dependence of the share of the EAEU in the structure of international trade of the member countries of this union on alternative management measures, which clarified the system of factors of cross-border cooperation of countries within the EAEU. The prospect is revealed and the author’s forecast for the development of cross-border cooperation between Russia and the EAEU member countries is compiled. The main conclusion is that innovation plays a decisive role in the development of cross-border cooperation: potential and growth guidelines in the EAEU. The theoretical significance of the results obtained and the conclusions based on them is due to the fact that they clarified the cause-and-effect relationships of cross-border cooperation between countries within the EAEU. The ineffectiveness of the customs approach to regulating international trade in the EAEU is substantiated due to the fact that a reduction in tariff rates does not lead to an increase in mutual trade in the union. As an alternative, a new approach to regulating international trade in the EAEU is proposed, which involves the development of an innovative economy. Of practical significance is the identified significant potential for the development of cross-border cooperation of countries within the EAEU, as well as the guidelines for the growth of mutual trade between Russia and the member countries of the union proposed for the most complete disclosure of this potential: increasing the high-tech level of exports by 52.03 % and imports by 998.90 %, growth in export activity of ICT services by 346.43 % and increase in patent activity by 164.55 %.